(3GdEYdGe HGdCYdGe Hjf GdMcGes - (3eMeO Hf ehSi, CHh YHO Gddg TeS GdOjf GHf GdfYeGf,J (B683 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aGfg dGMbkG YfO cGaI GdYbdG Cf GHf GdfaS GdbGHdI dfaY GdOfjG hGdCNQi Cf ge Edi GdCQV GdebOSI acJH Edjg SdeGf Ef GdCQV dGJbOS CMeO Ch EfeG hEfeG jbOS GdEfSGf Yedg s
(3BNQgG (B:s
(3cJHJ Edjc gPG GdcJGH JfHjgkG deG JbOe ef eMHJc hSejJ gPG GdcJGH cJGH GdEYdGe HGdCYdGe Hjf GdMcGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3eLGejY (B188) s
Keywords: (3abg GdePGgH GdCNQis